2010
DOI: 10.1186/1471-2407-10-203
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of preoperative serum vascular endothelial growth factor, interleukin-6, and C-reactive protein level in colorectal cancer

Abstract: BackgroundAngiogenesis is a multistep process in which many growth factors and cytokines have an essential role. Vascular endothelial growth factor (VEGF) is a potent angiogenic agent that acts as a specific mitogen for vascular endothelial cells through specific cell surface receptors. The interleukin-6 (IL-6) pathway is another mechanism linking angiogenesis to malignancy. C-reactive protein (CRP), a representative marker for inflammation, is known for its association with disease progression in many cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
66
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 38 publications
10
66
1
3
Order By: Relevance
“…CRP is an index of systemic inflammation and has been identified as a prognostic factor in patients with CRC and gastric cancer (24,25). However, serum CRP levels are not routinely assessed in the pre-operative assessment (12,14,18).…”
Section: Discussionmentioning
confidence: 99%
“…CRP is an index of systemic inflammation and has been identified as a prognostic factor in patients with CRC and gastric cancer (24,25). However, serum CRP levels are not routinely assessed in the pre-operative assessment (12,14,18).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Incidence of CRC has grown rapidly since 1990, and is influenced by eating and lifestyle habits that include increased meat intake and reduced fiber intake, alcohol consumption, or smoking. 4,5 The treatment of CRC has undergone substantial improvements in the last 10 to 15 years in terms of screening, surgical management of resectable disease, and adjuvant chemotherapy. Moreover, 5-year survival for all patients has improved from only 50% to 62% during the last 25 years.…”
Section: Introductionmentioning
confidence: 99%
“…Kwon et al reported that increased VEGF concentrations in colorectal cancer patients are an important prognostic factor when assessing life expectancy. 31 Altomare et al also suggested that patients, P = 0.003 and P = 0.005, respectively) and was the only independent prognostic factor in Stage II or Stage III patients (Stage II and Stage III, P = 0.001 and P = 0.03, respectively).…”
Section: Serum Vegf and Survival According To Cea Levelsmentioning
confidence: 99%